2018
DOI: 10.1007/s40292-017-0241-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Acetyl Salicylic Acid in Controlling the DOCA-Salt Induced Hypertension in Rats by Stimulating the Synthesis of r-Cortexin in the Kidney

Abstract: So, from this study it has been found that aspirin induces the r-cortexin synthesis in kidney cortex through the activation of eNOS in DOCA induced hypertensive rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…ASA treatment effectively prevented CIH-induced aortic remodeling changes on nearly all the measures that were evaluated. However, we should also note that this work has some limitations that will need to be explored in further studies: (i) Chronic ASA treatment could also be beneficial and attenuate the hypertension induced by CIH (Fletcher et al, 1992 ; Bosc et al, 2010 ), as recently reported in hypertensive rats (Maji et al, 2018 ). The occurrence of such sustained elevation of systemic blood pressure could be also an important contributor to the aortic remodeling induced by CIH.…”
Section: Discussionmentioning
confidence: 90%
“…ASA treatment effectively prevented CIH-induced aortic remodeling changes on nearly all the measures that were evaluated. However, we should also note that this work has some limitations that will need to be explored in further studies: (i) Chronic ASA treatment could also be beneficial and attenuate the hypertension induced by CIH (Fletcher et al, 1992 ; Bosc et al, 2010 ), as recently reported in hypertensive rats (Maji et al, 2018 ). The occurrence of such sustained elevation of systemic blood pressure could be also an important contributor to the aortic remodeling induced by CIH.…”
Section: Discussionmentioning
confidence: 90%
“…limitations that will need to be explored in further studies: (i) Chronic ASA treatment could also be beneficial and attenuate the hypertension induced by CIH (Fletcher et al, 1992;Bosc et al, 2010), as recently reported in hypertensive rats (Maji et al, 2018). The occurrence of such sustained elevation of systemic blood pressure could be also an important contributor to the aortic remodeling induced by CIH.…”
Section: Discussionmentioning
confidence: 92%